Moritz Graf von Dietrichstein - Kriehuber, Joseph, 1800-1878 (artist):::Creator:::::::::::: (Vienna; Austria; Gedr. bei Joh. Höfelich.)
Portrait of Moritz Graf von Dietrichstein surrounded by brown decorative border.